2018
DOI: 10.1007/s00464-018-6186-0
|View full text |Cite
|
Sign up to set email alerts
|

Totally endoscopic implant to effect a gastric bypass: 12-month safety and efficacy outcomes

Abstract: This study demonstrates the feasibility, safety, and efficacy of a fully trans-oral gastrointestinal bypass implant. This purely endoscopic device may provide a valuable addition to the armamentarium of treatment available for the management of morbid obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
3
0
2
Order By: Relevance
“…Implantation and removal of the device according to the study concepts was possible in all patients. EWL after one year was 44.8% [20].…”
Section: The Valentx and Its Successormentioning
confidence: 91%
“…Implantation and removal of the device according to the study concepts was possible in all patients. EWL after one year was 44.8% [20].…”
Section: The Valentx and Its Successormentioning
confidence: 91%
“…The latest generation of this device gave results of 17.6 TBWL% at 1 year. In another prospective study, a TBWL of 15.6% was observed at 6 months [100]. None of the studies reported hormones or gut peptides other than insulin resistance markers, so it is hard to make assumptions of the mechanism by which weight loss and insulin resistance is improved.…”
Section: Gastroduodenojejunal Bypass Sleevementioning
confidence: 99%
“…Moreover, mean HbA1c and fasting glucose decreased by 1.1% and 29 mg/dL, respectively, in the subgroup of patients with T2DM. The six most frequent AEs were epigastric pain, heartburn or acid reflux, regurgitation, vomiting, dysphagia, and nausea 26 . However, the device is undergoing substantial modifications 25,26 and no clinical trials of the GJBS are currently underway, possibly due to the complex and challenging implantation procedure and common AEs, including epigastric pain, heartburn or acid reflux, regurgitation, and vomiting.…”
Section: Small Intestine‐targeted Ebmts In Clinical Applicationmentioning
confidence: 99%